(untitled) (Journal of Hama University, 2025)
The research aims to test the effect of free trading ownership on the quality of the financial report, relying on the cash flow statement approach to measure total receivables, after controlling for bank size variables. The statistical population for the study represented (11) traditional banks listed on the Damascus Stock Exchange during the period from 2019 to 2022. Relying on simplex regression and the Statistical Package for the Social Sciences (SPSS, V.25) program to analyze the data and test the hypotheses. The results showed that there is an inverse effect of ownership structure as measured by free trading ownership in total receivables based on the cash flow statement approach, which means that there is a direct effect of free trading ownership on the quality of financial reports of banks listed on the Damascus Stock Exchange after controlling for the size of the bank.